STUDENTS CHALLENGES IN LEARNING ENGLISH ONLINE CLASSES - Widayanti, Ni Komang Ayu; Suarnajaya, I Wayan (Universitas Pendidikan Ganesha, 2021)
Not all teachers can operate computers or gadgets in online learning activities. Another problem is that the teacher finds it difficult to control every activity and student response to the material. This is due to the absence of learning discussions and the absence of students in the middle of the class. The purpose of this study is to analyze the challenges encountered during online English learning. This type of research is qualitative. This study uses library research methods with library research procedures guidelines. The technique used to collect data is the reduction technique—sources of data derived from scientific articles. The result of the study is that bold learning during the Covid-19 outbreak provides many challenges for students to follow. Internal factors can trigger external problems and vice versa. Internal factors that come from within students include motivation, learning attitudes, study habits, and personal practice. External factors that come from outside the students themselves are related to the environment around students. External factors include the media used by students and the environment in terms of financial problems and the learning environment. Therefore, online learning is still lacking, and other solutions are needed to improve the quality internally and externally.